THE ROLE OF 18F-FDG PET/CT IN FOLLOW UP OF LARYNGEAL CANCER AFTER TREATMENT: 18F-FDG PET/CT IN FOLLOW UP OF LARYNGEAL SCC - petrović, Jelena; Sobic Saranovic, Dragana; Milovanovic, Jovica; Jotic, Ana; Odalovic, Strahinja; Grozdic Milojevic, Isidora; Stojiljkovic, Milica; Artiko, Vera (Medical Research, 2023)
Introduction: The aim of this investigation was to estimate the diagnostic performance of positron emission tomography/computed tomography using fluorine-18 fluoro-deoxyglucose (18F-FDG PET/CT) in follow-up of post-treatment laryngeal squamous cell carcinoma (SCC) and survival rate. Material and methods: Fifty seven patients (50 males, 7 females), mean age (68.3±6.7), with post-treatment laryngeal SCC were investigated. Indications for 18F-FDG PET/CT were: post-surgery staging, post-therapy restaging with positive/uncertain CT, follow-up, suspected recurrence on CT. 18F-FDG PET/CT findings were compared to clinical follow-up of up to 10 years after imaging. Degree of metabolic activity was analyzed visually and semi-quantitatively using maximum standardized uptake value (SUVmax).Results: High accumulation of radiopharmaceutical was found in 41 (71.9%) patients who were considered true positive, physiological in 14 patients (24.5%) and only two males (3.5%) were false positive. Overall sensitivity of 18F-FDG PET/CT was 95.3%, specificity 100.0%, positive predictive value 100.0%, negative predictive value 87.5% and accuracy 96.5%. In 19 cases (33.3%) PET/CT findings significantly influenced further management of the patients. Progression-free survival (PFS) in the 18F-FDG positive group was 41.1±12.7 months. Statistically significant correlation between SUVmax and PFS was not observed (p>0.05). Conclusion: 18F-FDG PET/CT is a valuable tool for follow-up of laryngeal SCC due to its high sensitivity, specificity, PPV, NPV and accuracy. It can influence the patients’ management in significant number of cases. Patients with negative 18F-FDG PET/CT findings had longer PFS than those with positive ones, but without statistical significance. SUVmax was not proven to be a strong predictor of patients’ disease-free survival.
Keywords: Keywords: PET/CT, laryngeal carcinoma, 18F-FDG, SUVmax